2021
DOI: 10.3928/02793695-20201104-03
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mental Health Disorders Among Undergraduate University Students in the United States: A Review

Abstract: The aim of the current review is to describe the prevalence and demographic correlates of mental health disorders among undergraduate university students in the United States. A search strategy was built and conducted using PubMed, PsycINFO, and CINAHL to identify studies published between 2009 and 2019 on the prevalence of mental health disorders, as defined in the fourth and fifth editions of the Diagnostic and Statistical Manual of Mental Disorders , in undergraduate students in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 36 publications
0
11
0
2
Order By: Relevance
“…The pandemic has been an important stressor that may have compromised the mental health of college students and changed their lifestyles with significant consequences on their well-being and academic performance. Several studies have shown that college students present poorer mental health compared to their peers in the general population (Kang et al, 2021 ; Lovell et al, 2015 ), and the COVID-19 pandemic may have been a stressor that further worsened the mental health conditions of college students. However, the empirical link between COVID-19 pandemic and college students’ mental health has not been established clearly.…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic has been an important stressor that may have compromised the mental health of college students and changed their lifestyles with significant consequences on their well-being and academic performance. Several studies have shown that college students present poorer mental health compared to their peers in the general population (Kang et al, 2021 ; Lovell et al, 2015 ), and the COVID-19 pandemic may have been a stressor that further worsened the mental health conditions of college students. However, the empirical link between COVID-19 pandemic and college students’ mental health has not been established clearly.…”
Section: Introductionmentioning
confidence: 99%
“…In the current case, ventricular dilatation and hypertrophy were present but seem rather related to manifest signs of chronic hypertension. In contrast, myocardial inflammatory reactions had been well-linked to gene-based COVID-19 vaccinations in numerous cases [ 9 , 35 , 36 , 37 ]. In one case, the spike protein of SARS-CoV-2 could also be demonstrated by immunohistochemistry in the heart of vaccinated individuals [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…College students go through a crucial period of transition from late-adolescence to adulthood, when they have to deal with various stressful tasks. This period of development is considered a sensitive age for the onset of common psychiatric conditions (Kang, Rhodes, Rivers, Thornton, & Rodney, 2021;Kessler et al, 2005;Liu, Stevens, Wong, Yasui, & Chen, 2018;Patel, Flisher, Hetrick, & McGorry, 2007). The WHO World Mental Health International College Student project displayed that one in three college students screened positive for at least one of the common lifetime mental disorders, showing a high level of need for mental health services in university contexts (Auerbach et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The WHO World Mental Health International College Student project displayed that one in three college students screened positive for at least one of the common lifetime mental disorders, showing a high level of need for mental health services in university contexts (Auerbach et al, 2018). Furthermore, several evidences found that college students present poorer mental health as compared to their peers in the general population (Blanco et al, 2008;Bruffaerts et al, 2019;Kang et al, 2021;Lovell, Nash, Sharman, & Lane, 2015;Rith-Najarian, Boustani, & Chorpita, 2019). Also, alcohol/substance use disorders are highly prevalent among college students (Bruffaerts et al, 2019;Cordero-Oropeza, García-Méndez, Cordero-Oropeza, Corona-Maldonado, 2021;Skidmore, Kaufman, & Crowell, 2016), which eventually may lead to suicide or attempted suicide, an ever-growing issue of concern in academic settings (Gunnel, Caul, Appleby, John, & Hawton, 2020;Mortier et al, 2018;Oh, Marinovich, Jay, Zhou, & Kim, 2021;WHO, 2016).…”
Section: Introductionmentioning
confidence: 99%